2014
DOI: 10.1667/rr13731.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining Molecular Signature of Pro-Immunogenic Radiotherapy Targets in Human Prostate Cancer Cells

Abstract: To understand the impact of clinically relevant radiation therapy (RT) on tumor immune gene expression and to utilize the changes that occur during treatment to improve cancer treatment outcome, we examined how immune response genes are modulated in prostate cancer cells of varying p53 status. LNCaP (p53 wild-type), PC3 (p53 null) and DU145 (p53 mutant) cells received a 10 Gy single dose or 1 Gy × 10 multifractionated radiation dose to simulate hypofractionated and conventionally fractionated prostate radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…Conversely, use of higher doses of radiation, namely ≥15 Gy, increased the fraction of splenic regulatory T (T REG ) cells, which function to suppress tumour-specific immunity 26 . The importance of the radiation dose and fractionation schedule used was further corroborated in a study showing activation of immune-response-related genes, radiation-induced damage-associated molecular pattern molecules (DAMPs), and inflammatory cytokines in human prostate cancer cells when exposed to radiation in the range of 8–10 Gy 27 . Thus, these data suggest the existence of a threshold dose below which immune stimulation might be suboptimal and above which immunosuppression prevails.…”
Section: Preclinical Evidencementioning
confidence: 93%
“…Conversely, use of higher doses of radiation, namely ≥15 Gy, increased the fraction of splenic regulatory T (T REG ) cells, which function to suppress tumour-specific immunity 26 . The importance of the radiation dose and fractionation schedule used was further corroborated in a study showing activation of immune-response-related genes, radiation-induced damage-associated molecular pattern molecules (DAMPs), and inflammatory cytokines in human prostate cancer cells when exposed to radiation in the range of 8–10 Gy 27 . Thus, these data suggest the existence of a threshold dose below which immune stimulation might be suboptimal and above which immunosuppression prevails.…”
Section: Preclinical Evidencementioning
confidence: 93%
“…Two genes overlapped between the two irradiation modalities, while the other 3 genes were involved in inflammatory responses by T cells and macrophages. 157 This study clearly demonstrated that the different irradiation modalities and doses not only induced a different activation level of the genes, but also the pattern of activated genes and thus the initiated immune and inflammatory mechanisms differed. Very similar results were obtained by Palayoor et al in human coronary artery endothelial cells.…”
mentioning
confidence: 68%
“…157 Their data showed that multifractionated doses could activate immune response genes more robustly than single-dose treatment, with a relatively larger number of immune genes upregulated in p53-null cells compared to wild-type or p53 mutant cells. Although both single dose (1 × 10 Gy) and multifractionated dose (10 × 1 Gy) altered DAMPs and cytokine levels, the effect was more pronounced with multifractionated treatment.…”
mentioning
confidence: 99%
“…Therefore, it is important to understand how immune genes respond to survival adaptation of irradiated tumor cells (during multifractionation as well as after single high-dose fraction) to best exploit radiation for combined immunotherapy approaches. Aryankalayil et al ( 2 ) demonstrated that both multifractionated as well single-dose radiation induced DAMPs and positively modulated the cytokine environment, with more observed in multifractionated radiotherapy. Kanagavelu et al ( 3 ) demonstrated the presence of immune modulation in partially irradiated contralateral syngeneic lung tumors.…”
Section: Radiation-induced Immunomodulationmentioning
confidence: 99%